Onchocerca volvulus: Genetic Diversity of Parasite Isolates from Sudan - Higazi, Tarig B.; Katholi, Charles R.; Mahmoud, Babiker M.; Baraka, Omer Z.; Mukhtar, Moawia M.; Qubati, Yassin Al; Unnasch, Thomas R. (Experimental parasitology, 2001)
Higazi, T. B., Katholi, C. R., Mahmoud, B. M., Baraka, O. Z., Mukhtar, M. M., Qubati, Y. A., and Unnasch, T. R. 2001. Onchocerca volvulus: Genetic diversity of parasite isolates from Sudan. Experimental Parasitology97, 24–34. Onchocerciasis in Sudan exists in three distinct foci which exhibit differing clinical presentations. Previous studies have demonstrated that a tandemly repeated Onchocerca sequence family with a unit repeat length of 150 bp (the O-150 family) is a useful marker for deducing relationships among different O. volvulus populations. In the current study, the O-150 repeat families of O. volvulus from Sudan were analyzed and compared to each other and to those of parasites from West Africa. Similar to West African and American O. volvulus, the O-150 families of the Sudanese parasites could be divided into clusters within which little or no intracluster variation was evident, suggesting that the O-150 family in these parasites was subject to the forces of concerted evolution. Statistical analysis of the O-150 families from the different Sudanese parasite isolates, employing a nested algorithm based on an analysis of variance, revealed that O. volvulus endemic to the northern focus at Abu Hamed were significantly different from all other O. volvulus populations examined to date. In contrast, parasites from the southern and eastern foci of Sudan were indistinguishable from those endemic to the West African savanna. The significance of these data are discussed in light of knowledge of the biogeography and biology of transmission of O. volvulus in Africa.